The Effectiveness of Cooperative Learning Integrated with Huyula Values and Variety of Media to Improve Science Mastery in Inclusive Environments - Odja, Abdul Haris; Doung, Ratha; Pikoli, Masrid; Yunus, Rasid; Mohamad, Wahyu Mu'zizat; Mursalin (Universitas Negeri Semarang, 2025)
Science learning in public schools should be designed to accommodate both regular students and students with special education needs. This is also one of the implementations of SDG 4, Sustainable Development, specifically related to quality education and inclusive education. This study aims to measure the effectiveness of cooperative learning integrated with local wisdom values of Huyula in improving science concept mastery among regular students and students with special education needs in public schools. The study employs a pre-experimental design with a one-group, pretest-posttest approach. The study was conducted in five schools involving 323 regular students and 12 students with special education needs. The research results on the effectiveness of cooperative learning integrated with the local wisdom values of Huyula showed a significant increase in science concept mastery. This is indicated by the hypothesis test through the Wilcoxon signed-rank test with a value of z = -15.84, through the N-Gain test (high category, average 0.74), and a strong effect size through the rank-biserial correlation value (-1.00). This study concludes that the implementation of science learning integrated with Huyula values and media variety has an influence and is effective in improving the science concept mastery of regular students in the high category and students with special education needs in the medium category. This finding highlights the importance of integrating local wisdom values and media variety in supporting the improvement of science concept mastery through meaningful and inclusive teaching for all students.